2015
DOI: 10.1111/ped.12653
|View full text |Cite
|
Sign up to set email alerts
|

Urinary screening and urinary abnormalities in 3‐year‐old children in Japan

Abstract: In Japan, urinary screening for preschool children has been obligatory since 1961. The system was reconsidered and has been under review since 2012, because many problems in the system had been identified, and its usefulness was uncertain. In the process, the following were analyzed: (i) frequency of urinary abnormalities identified on screening; (ii) diseases identified from urinary abnormalities; (iii) clinical course of children found to have urinary abnormalities; and (iv) screening for asymptomatic urinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 8 publications
0
7
0
1
Order By: Relevance
“…On the other hand, immediate attention should be given to children with proteinuria as it usually reflects diseases requiring intervention. 10 Positive urine dipsticks for proteinuria should be confirmed by laboratory measurement of urine protein to creatinine ratio. 11 There is once again a scarceness in the number of studies carried out in the Kingdom of Saudi Arabia regarding the prevalence of pediatric hematuria as there are only 2.…”
mentioning
confidence: 99%
“…On the other hand, immediate attention should be given to children with proteinuria as it usually reflects diseases requiring intervention. 10 Positive urine dipsticks for proteinuria should be confirmed by laboratory measurement of urine protein to creatinine ratio. 11 There is once again a scarceness in the number of studies carried out in the Kingdom of Saudi Arabia regarding the prevalence of pediatric hematuria as there are only 2.…”
mentioning
confidence: 99%
“…The study by Yanagahira reported that false positives are common in leucocyturia examination using a dipstick. 24 Another study reported that postoperative bacteriuria was a common phenomenon found in up to 51% cases, and thus broad-spectrum prophylaxis and postoperative antibiotics were recommended in order to decrease the risk of UTI which may contribute to fistula formation. 23 Other studies reported that pre-and postoperative positive swab results may contribute to wound infection and suggested antibiotic therapy based on the preoperative perimeatal swab.…”
Section: Discussionmentioning
confidence: 99%
“…El tratamiento y pronóstico de la hematuria depende de la causa desencadenante del proceso primario. El pronóstico de la hematuria en la niñez es benigno en un alto porcentaje, sobre todo en los preescolares, en los cuales se ha demostrado que presentan hematuria en el primer examen de orina en el 8,2% de los casos y en el tercer uroanálisis de confirmación esta prevalencia disminuye al 0,5% [28]. En otras poblaciones el porcentaje de hematuria significativa en la primera muestra ha sido tan solo del 0,8% [52].…”
Section: Tratamiento Y Pronósticounclassified